Is carbon risk priced in the cross-section of corporate bond returns? - DUAN, Tinghua (Institutional Knowledge at Singapore Management University, 2023)
This paper examines the pricing of a firm's carbon risk, measured by its carbon emissions intensity, in the cross-section of corporate bond returns. Contrary to the "carbon risk premium" hypothesis, we find bonds of firms with higher carbon emissions intensity earn significantly lower returns. This effect cannot be explained by a comprehensive list of bond characteristics and exposure to known risk factors. Investigating sources of the low carbon premium, we find the underperformance of bonds issued by carbon-intensive firms cannot be fully explained by divestment from institutional investors. Instead, our evidence is most consistent with investor underreaction to carbon risk, as carbon emissions intensity is predictive of lower future cash flow news, deteriorating firm creditworthiness, and more frequent environmental incidents.